Solution
Given the equation below:
[tex]x(x+6)=91[/tex]
Using the completing the square:
[tex]\begin{gathered} x(x+6)=91 \\ x^2+6x-91=0 \\ half\text{ the coefficient of x, square and add to both side} \\ x^2+6x=91 \\ x^2+6x+(3)^2=91+(3)^2 \\ (x+3)^2=91+9 \\ (x+3)^2=100 \end{gathered}[/tex]
Square root both side of the equation
[tex]\begin{gathered} (x+3)^2=100 \\ \sqrt{(x+3)^2}=\pm\sqrt{100} \\ x+3=\pm10 \\ x=\pm10-3 \\ x=7,x=-13 \end{gathered}[/tex]
Therefore the equivalent equations in the appropriate order is